Silencing of Glucose Transporter Protein-1 by RNA Interference Inhibits Human Osteosarcoma Mg63 Cells Growth in vivo. (April 2015) - Jian, Fan; Yuan, Feng; Jiong, Mei; Zhu, Xiao-zhong; Yu, Guang-rong; Lu, Dong-dong
While knock-down of glucose transporter protein 1 (GLUT-1) inhibited various human cancer cell growth in vitro and in vivo, including osteosarcoma cell growth in vitro, there has been no report on whether knock-down of GLUT-1 by siRNA may inhibit osteosarcoma cell growth in vivo . We hypothesized that siRNA may inhibit osteosarcoma cell growth in vivo . We introduced siRNA-GLUT-1 by lentivirus into MG63 osteosarcoma cells which were xenograted into nude mice. Immunohistochemical staining, Western blot and reverse transcriptase quantitative (RT-qPCR) were used to determine GLUT-1 protein and mRNA expression of the tumor cells. The results showed the tumor volume of GLUT-1-siRNA-MG63 cells xenorafted nude mice was significantly less than that of siGFP-MG63 or MG63 cells xenografted nude mice ( P < 0.05), suggesting that silencing of GLUT-1 inhibited tumor formation and growth of osteosarcoma cells in vivo . Our findings suggest that the lentiviral-mediated siRNA interference against GLUT-1 may be a valuable tool for gene therapy for osteosarcoma.